Matemática financeira no cotidiano dos brasileiros - Silva, Conrado Valdovando da (Universidade Federal de São Carlos, 2021)
This monograph is a study of topics on Financial Education – its history, the nowadays brazilian panorama on this subject, the National Strategy on Financial Education (ENEF) and the DICTs (Digital Information and Communication Technologies) with teaching-learning potential for Financial Mathematics as for example the spreadsheets environment of GeoGebra and the Calculadora do Cidadão (Citizen Calculator). The work also suggests activities about the resolution of financial problems with the support of the previously mentioned softwares.
Financial mathematics in daily Life of brazilians
Keywords: Educação Financeira; Calculadora do cidadão; GeoGebra; Resolução de problemas; CIENCIAS EXATAS E DA TERRA::MATEMATICA